TACE combined with microwave ablation therapy vs. TACE alone for treatment of early- and intermediate-stage hepatocellular carcinomas larger than 5 cm: a meta-analysis - Chong Liu; Tian Li; Jin-tong He; Haibo Shao (Diagnostic and Interventional Radiology, 2020)

(untitled)
There are many therapeutic options for primary hepatocellular carcinoma (HCC), but very limited options for unresectable HCC with a single lesion larger than 5 cm (Barcelona Clinic Liver Cancer [BCLC] stage A) or with 2-3 nodules beyond 5 cm (BCLC stage B). Transcatheter arterial chemoembolization (TACE) is considered the first-line treatment for these patients, and combination therapy has also been tried. However, the effectiveness of microwave ablation (MWA) combined with TACE in the treatment of the above tumors remains to be further confirmed. Therefore, this meta-analysis aimed to compare the effectiveness of combination therapy and TACE monotherapy on these patients. PubMed, Cochrane Library, Embase, China National Knowledge Infrastructure, and the Wan Fang electronic databases were retrieved to search for studies comparing combination therapy and TACE monotherapy, published between the earliest available date and August 20, 2019. A total of 20 articles (reporting 1736 patients) were included. Meta-analysis showed that, compared to TACE alone, TACE + MWA resulted in significantly higher 1-, 2-, and 3-year overall survival (OS) (1-year OS rate: RR = 1.36, 95% CI 1.28–1.44, P < 0.001; 2-year OS rate: RR = 1.56, 95% CI 1.40–1.74, P < 0.001 and 3-year OS rate: RR = 2.07, 95% CI: 1.67–2.57, P < 0.001). Complete response, partial response, and objective response rates were significantly higher in TACE + MWA than those in TACE alone (P < 0.001). Meanwhile, publication bias and sensitivity analysis were performed and did not show statistical significance.